The Effect of COVID-19 Lockdown Measures on Internet Speed : An Empirical Analysis of 18 Countries in Africa - World Bank (World Bank, Washington, DC, 2021)
Coronavirus (COVID-19) and the related lockdown measures to prevent the virus’ spread have highlighted how important it is for everyone to have access to reliable and resilient digital infrastructure. Restrictions on movement have generated higher Internet usage and increased traffic on networks, reflecting an increase in remote working and learning, as well as other activities that have shifted online. This article provides insight into the effect of Coronavirus (COVID-19) related lockdown measures on internet speed in a sample of developing countries in Africa. The findings of this study demonstrate the resiliency of digital infrastructure in Africa and also highlight and reflect the benefits of partnership between public and private stakeholders to manage traffic surges. The development community should encourage and leverage these partnerships to not only ensure continued network resilience during times of crisis, but also to minimize the digital divide between countries and within countries as the new global digital transformation takes shape.